Construction Grammar Meets Language Testing and Evaluation: Redefining & Ensuring Construct Validity - Gedik, Tan Arda (Institut Agama Islam Negeri Kudus, 2022)
Theoretical linguistics and teaching are concurrent, that is, neither can exist without the other. In other words, decisions made in (foreign) language teaching will inevitably affect how language testing and evaluation as a concept is designed and administered. For example, if a curriculum states that the English as a foreign language teachers need to make a distinction between a gerund and an infinitive in the classroom and teach it as such, then, this distinction will be tested or evaluated in one way or another. In this article, language testing and evaluation (LTE), an important component in language teaching, is combined with construction grammar (henceforth CxG), a salient theory of language with ample evidence to support its claims. Specifically, this article discusses how construct validity, test items, and rubrics can be reimagined from the perspective of usage-based construction grammar.